The Influence of Professional Recommendation, Brand Image, and Price Perception on Purchase Intention of Scarlett Whitening Products Among Generation Z in Bandar Lampung City - Aulia Sisca; Lestari Wuryanti; Ayu Nursari (Yayasan Multidimensi Kreatif, 2026)
This study aims to examine the influence of professional recommendation, brand image, and price perception on the purchase intention of Scarlett Whitening products among Generation Z in Bandar Lampung City. The research utilizes a quantitative approach with a survey method. The population consists of undergraduate medical students from Universitas Lampung and Universitas Malahayati, with a sample of 315 respondents selected through purposive sampling. Data were collected via questionnaires using a Likert scale and analyzed using multiple linear regression assisted by SPSS software. The results indicate that professional recommendation and brand image partially have a positive and significant effect on purchase intention. Conversely, price perception exhibits a significant negative effect, indicating that higher perceived prices lead to lower purchase intention. Simultaneously, professional recommendation, brand image, and price perception significantly influence the purchase intention of Scarlett Whitening products. These three independent variables collectively explain 59.1% of the variance in purchase intention, while the remaining 40.9% is influenced by other external factors not examined in this study.